Pengaruh Penerapan Metode Mind Mapping terhadap Hasil Belajar Mata Kuliah Bahasa Inggris pada Mahasiswa D-III Kebidanan Tingkat I Poltekes Bhakti Pertiwi Husada - Fatimah, Siti; Pipih, Ade (Jurnal Kesehatan Pertiwi, 2022)
Introduction: The mind map is a creative recording method that allows us to remember a lot of information. Mind mapping or mind map is the most effective and efficient way to enter, store and extract data from / to the brain. Mind mapping is an easy way to extract information from inside and outside the brain. In the mind map, the brain's working system is naturally regulated. Automatic work was in accordance with the naturalness of human thinking. Map of the mind to make the human brain well explored, and work according to its function. Purpose: The purpose of this study is to determine the effect of Mind Mapping Method Implementation on Learning Results of English Course in Students D III Midwifery Level I Poltekes Bhakti Pertiwi Husada Cirebon Year 2021. Method: Type of research using experimental research technique is where the researcher do treatment (treatment) to a group of research sample and research design experiment pretest-posttest control group desaign. Sampling is determined by purposive sampling technique that is non-random sampling technique based on certain considerations. The sample of this research is 14 D3 Midwifery students of Poltekes BPH Cirebon. Result: The result of this research concludes that the application of mind mapping learning method on English Course D3 Midwifery students of Poltekes BPH Cirebon is 12,5% good, 50,0% enough and 37,5% less. The learning result before mind mapping is 31.2% good, 43.8% is enough and 25.5% less and after mind mapping is 56.2% good, 43.8% is enough and 0.0% less. There is influence of applying mind mapping method toward learning outcomes in DIII students of Midwifery Poltekes BPH Cirebon with t = 3,994 and p-value = 0,028.